Diabolical Possession and the Case Behind The Exorcist: An Overview of Scientific Research with Interviews with Witnesses and Experts by Sergio A. Rueda - Kruth, John G. (Journal of Scientific Exploration, 2019)
Outside of Washington, D.C. in the town of Mount Rainier, Maryland, an episode of potential demonic possession was investigated by the Catholic Church and the Duke Parapsychology Lab, including the famous scientist, J.B. Rhine. The episode, which involved a 14 year old boy, was reported in the Washington Post in 1949. As is the case with most claims of possession, in order to protect the identity of the family involved, the church maintained a wall of secrecy around the specific events and the activities of the clergy who investigated this case. Twenty years later, William Peter Blatty (1971) produced a fictionalized novel featuring a young girl who was possessed by a demon and had to undergo the religious ritual of exorcism to be cleansed and to stop a horrifying series of events. The book was called The Exorcist. In 1973, the novel was produced as the film The Exorcist which won the screenwriter, William Peter Blatty, an Academy Award for Best Adapted Screenplay. The film horrified audiences, caused many viewers to walk out of the theater in disgust, and elicited worldwide protests from religious leaders. Many years later, it is still considered one of the most terrifying horror movies ever made despite its antiquated special effects. But, the real questions on the mind of nearly every person who saw the film were, “Has anyone really been possessed by the devil?”, and “Is this based on a true story?” Sergio Rueda explores these questions and attempts to uncover the actual facts and observations of the 1949 case that appears to be the story behind The Exorcist.